Efficacy of Computer‐Based Telephone Counseling on Long‐Term Adherence to Strength Training in Elderly Patients With Knee Osteoarthritis: A Randomized Trial. Issue 7 (29th June 2020) - Baker, Kristin; LaValley, Michael P.; Brown, Carrie; Felson, David T.; Ledingham, Aileen; Keysor, Julie J.
Abstract : Objective: To determine whether the Boston Overcoming Osteoarthritis through Strength Training Telephone‐Linked Communication (BOOST‐TLC) program, a novel telephone‐based, motivational, strength‐training exercise‐adherence counseling intervention, improved adherence to a strength‐training exercise program over 2 years. Methods: Participants were recruited for this 2‐year, single‐blind, parallel‐arm randomized controlled trial from knee osteoarthritis patient registries, community newspapers, and online websites in Massachusetts. Eligibility criteria included age 50 years or older, painful knee osteoarthritis, and ability to use a telephone. Exclusion criteria included medical conditions precluding exercise, inflammatory arthritis, current regular strength training, planned knee replacement surgery, dementia, inability to follow exercise instructions, and inability to use the TLC system. After participating in a group exercise class, participants were randomized to receiving motivational telephone calls through the BOOST‐TLC program for 24 months or the control. Both control and intervention participants received a monthly automated phone message reminder to continue the program. Exercise adherence was ascertained by a single self‐report item scored 0–10, where 10 represented complete adherence. Outcomes were evaluated at 6, 12, 18, and 24 months. Results: A total of 104 subjects were randomized, and 89 subjects (44 control, 45 TLC) completed the 24‐month follow‐up. There was no significant difference in adherence at 24 months between groups (mean for control group 4.01 [95% confidence interval (95% CI) 3.03, 4.99], mean for TLC subjects 3.63 [95% CI 2.70, 4.56]; P = 0.57). Conclusion: In those with knee osteoarthritis who had participated in an exercise program, frequent motivational telephone reminders did not increase adherence to strength‐training exercise.